Pediatric Metronidazole-Induced Encephalopathy: A Case Report and Review of the Literature - Cappellari, Alberto M.; Rossetti, Donata; Avignone, Sabrina; Scola, Elisa; Di Cesare, Antonio (Journal of Pediatric Neurology, 2020)
Metronidazole-induced encephalopathy is a rare toxic encephalopathy secondary to the common use to this antimicrobial drug. It has been reported mainly in adult patients but only rarely in children. Owing to possible devastating complication of this disease, clinicians should have a higher index of suspicion for encephalopathic patients on metronidazole therapy. Here, we report a 5-month-old infant with metronidazole-induced encephalopathy presenting with nonconvulsive status epilepticus. A review of the literature in pediatric, as well as adult metronidazole-induced encephalopathy, is also provided.
Keywords: metronidazole; encephalopathy; nonconvulsive status epilepticus